Net Working Capital and Growth Opportunity on Cash Holding - Ulfa, Maria; Dasman, Sunita; Sapruwan, Muhammad; Gea, Fransiskus; Ristyaningsih , Ristyaningsih; Kurniawati, Marenda (Growth: Journal Management and Business, 2023)
The presence of cash in a company's balance sheet is an important component. Without cash, the company's activities can’t run. This study aims to analyze and provide empirical evidence related to the effect of net working capital and growth opportunity on cash holding in automotive and component subsector companies listed on the Indonesia Stock Exchange in 2017-2021. This study uses secondary data with data analysis method using panel data regression analysis. The sample used in this study used a non-probability sampling technique with a saturated sampling technique method and obtained 12 samples. The results of this study indicate that net working capital has a significant effect on cash holding, while growth opportunity has no significant effect on cash holding.